2013
DOI: 10.1021/ie3020473
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Evaluation of Surface Properties of Cyclohexanoxycarbonylmethylpyridinium and Cyclohexanoxycarbonylmethylimidazolium Ionic Liquids

Abstract: TABLE OF CONTENT Graphs of specific conductivity vs concentration NMR, Mass and IR spectra of ionic liquids Graph of thermal stability and X-Ray crystallographic data of ionic liquids 1 H spectra of N-(cyclohexanoxycarbonylmethyl)pyridinium bromide (9a) 13 C spectra of N-(cyclohexanoxycarbonylmethyl)pyridinium bromide (9a)6 13 C spectra of 3-methyl-N-(cyclohexanoxycarbonylmethyl)imidazolium bromide (13a) 13 C DEPT spectra of 3-methyl-N-(cyclohexanoxycarbonylmethyl)imidazolium bromide (13a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…For both series of amide-functionalized ionic liquids (C n AMeImBr and C n APyrBr) the cmc decreases with increasing the alkyl chain length ( Table 2). This behaviour is analogous to that reported for different functionalized [19,20,26,33] and non-functionalized amphiphilic ILs [14,16,36,37], as well as for ionic surfactants [38][39][40].…”
Section: Conductivity Measurementssupporting
confidence: 86%
See 1 more Smart Citation
“…For both series of amide-functionalized ionic liquids (C n AMeImBr and C n APyrBr) the cmc decreases with increasing the alkyl chain length ( Table 2). This behaviour is analogous to that reported for different functionalized [19,20,26,33] and non-functionalized amphiphilic ILs [14,16,36,37], as well as for ionic surfactants [38][39][40].…”
Section: Conductivity Measurementssupporting
confidence: 86%
“…The plots for the rest of the amide-functionalized ILs studied are given in the Supplementary data (Appendix A). cmc the rate augmentation of the specific conductivity is lower because the micelles can contribute to the charge transport to a lesser extent than the free ions owing to their lower mobility and to the effective loss of ionic charge as a result of the binding of a fraction of counterions to the micellar surface [20,33,34]. The counterion binding parameter (β) gives the extent of counter ion association and can be estimated from the ratio of the slopes above and below the cmc [35].…”
Section: Conductivity Measurementsmentioning
confidence: 99%
“…A recent survey on the value of CMC of different ionic liquids has shown that alteration in the structure of the cationic head group leads to the reduction in the value of CMC. Introduction of different types of functional groups, like, alcohol (Chauhan et al, ), ester (Aggarwal et al, ; Aggarwal and Singh, ), or amide (Kanjilal et al, ), into the cationic head groups affects the value of CMC considerably. The surface tension measurements not only measure the CMC, but also provide many other physicochemical parameters.…”
Section: Resultsmentioning
confidence: 99%
“…[1,2] They manifest interesting physicochemical properties like high thermal stability, high conductivity, negligible low vapor pressure and non-flammability. [3][4][5] A modified form of ILs known as surface-active ionic liquids (SAILs) possessing desirable combined characteristics of both ILs and surfactants have been introduced. [6] Analogous to conventional ionic liquids (ILs), properties of SAILs can be adjusted by selecting the proper cation and anion combination.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs) are mainly composed of ions (cations and anions) with melting points below 100 °C and have emerged as intriguing substitutes for traditionally used volatile organic solvents [1,2] . They manifest interesting physicochemical properties like high thermal stability, high conductivity, negligible low vapor pressure and non‐flammability [3–5] . A modified form of ILs known as surface‐active ionic liquids (SAILs) possessing desirable combined characteristics of both ILs and surfactants have been introduced [6] .…”
Section: Introductionmentioning
confidence: 99%